Kemampuan Sabun Antiseptik Cair yang Mengandung Triclosan yang Terdaftar di BPOM dalam Menghambat Pertumbuhan Bakteri Escherichia coli - Marhamah Marhamah; Sri Ujiani; Maria Tuntun (Politeknik Kesehatan Tanjung Karang, 2019)
In the community, there is still circulating hand washing soap containing triclosan and registered with BPOM/Ministry of Health, but the packaging is not printed how many milliliters of water should be added so that the concentration is not effective in killing bacteria on the hand. The purpose of this study was to determine the ability of liquid antiseptic soap containing triclosan registered at BPOM/Ministry of Health in inhibiting the growth of Escherichia coli bacteria and bacteria on the hands. The research was carried out at the Bacteriology Laboratory of the Department of Health Analyst at Tanjungkarang Health Polytechnic and Lampung Veterinary Center in July-November 2017. This type of research was a completely randomized design. Pre-experiment of one group pre-post-test, the test method of Total Plate Numbers (ALT). Test uses concentrations of 2%, 4%, 6%, 8% and 10% with 5 repetitions. The results showed the strength of liquid antiseptic soap containing triclosan with a concentration of 2%, 4%, 6%, 8% and 10% including the criteria of being moderate and effective in killing bacteria on the hand with a decrease in germ number 96.18%. The Anova test obtained p-value 0,000, meaning that there was an effect of the concentration of liquid antiseptic soap on the growth of Escherichia coli bacteria. The LSD test results showed a significant difference between each liquid antiseptic soap concentration (p-value 0,000-0,024) in inhibiting bacterial growth. The results of the T-test showed that there were differences in the number of germs (ALT) in the hands before and after hand washing with liquid antiseptic soap.